Our endangered values : America's moral crisis - Carter, Jimmy frey50 (New York : Simon and Schuster, 2005)
President Carter has written importantly about his spiritual life and faith. In this book, he offers a personal consideration of "moral values" as they relate to the important issues of the day. He put
Keywords: Social values-zUnited States; Religious fundamentalism-zUnited States; Christianity and politics-zUnited States; Church and State-zUnited States; Church and social problems-zUnited States; Human rights-xGovernment policy-zUnited States; United States-xPolitics and government-y2001-xmoral and ethical aspects; United States-xForeign relations-y2001-xmoral and ethical aspects; United States-xMoral conditions